Praise of Editor - Yalçın Yalçınkaya (Türk Kütüphaneciliği)
This study investigates the issue of editorship and emphasizes the function and significance of editor within the scope of scientific publication. The editor is important on the mathematical objectivity and scientific validity of a scientific work and it is effective and influential in the transformation of one-dimensional information to three-dimensional information. An editor believes in the future with innovation and works for the permanence of information.